Quantum oscillator in an infinite-particle harmonic system - Rozhenko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The behavior of a quantum oscillator in an infinite-particle system is studied for the case of linear interaction. The relation between the spectrum of the dynamic matrix of a complete system and oscillator damping is established. The dependence of the spectrum on the parameters of interaction is determined.